Keluarga Rancangan Allah Dan Implikasinya Dalam Pedidikan Keluarga Kristen - Tri Astuti Yeniretnowati; Yakub Hendrawan Perangin Angin (Sekolah Tinggi Teologi Tenggarong, 2021)
Many problems occur in Christian marriages and families. One of the main causes of the many problems that plague Christian marriages and some divorces is the lack of understanding of the meaning of the vision and mission of marriage as God's design. Christian marriage vocation should reflect a holistic unity. Christian families must be alert to the challenges they face. The method in this research is a qualitative methodology with a literature study approach. As for the results of this study, there are five implications of understanding the meaning of the vision and mission of the family designed by God in Christian family education, namely: First, the means for parents to help children's perspective. Second, build a strong and healthy and successful marriage vision. Third, make wise marriage choices. Fourth, take root, grow, and bear fruit with a partner. Fifth, serve the couple.Abstrak:Banyak permasalahan terjadi dalam pernikahan dan keluarga Kristen. Salah satu penyebab utama banyaknya persoalan yang melanda pernikahan Kristen dan beberapa perceraian karena kurangnya memahami makna visi dan misi pernikahan sebagai rancangan Allah. Panggilan pernikahan Kristen seharusnya dapat mencerminkan kesatuan yang besifat holistis. Keluarga Kristen harus waspada terhadap tantangan yang dihadapi. Metoda dalam penelitian ini adalah dengan metodologi kualitatif pendekatan studi pustaka. Adapun hasil dari penelitiam ini adanya lima implikasi dari pemahaman makna visi dan misi keluarga rancangan Allah ini dalam pendidikan keluarga Kristen yaitu: Pertama, Sarana orang uua membantu cara pandang anak. Kedua, Membangun visi pernikahan yang kuat dan sehat serta berhasil. Ketiga, Membuat pilihan pernikahan yang bijak. Keempat, Berakar, bertumbuh, dan berbuah bersama pasangan. Kelima, Melayani pasangan